Role of LiF additive on spark plasma sintered transparent YAG ceramics. Issue 17 (1st December 2017) - Katz, Aurélien; Barraud, Elodie; Lemonnier, Sébastien; Sorrel, Emmanuel; Eichhorn, M.; d'Astorg, Sophie; Leriche, Anne
Abstract: It is well known that the presence of LiF as sintering aid to process transparent polycrystalline Y3 Al5 O12 (YAG) ceramics by the Spark Plasma Sintering (SPS) technique induces three positive effects: a better particle rearrangement, a higher densification rate and the elimination of carbon contamination leading to the improvement of the material optical properties. However, the reaction mechanisms responsible of these effects still need to be clarified. Two YAG powders presenting different characteristics were selected to highlight the possible interaction between impurities and the sintering aid. In order to facilitate the determination of the LiF action during processing and reveal the involved phenomena, an excessive quantity of 5 wt% LiF was added. Samples were sintered at different temperatures between 800 °C and 1450 °C under 50 MPa. XRD, SEM and EDX techniques were used to characterise the microstructural development of ceramics and to establish the mode of action of LiF. The results highlighted that the role of LiF is mainly dependent on the purity and the phase composition of starting powders and that the SPS cycle must be adapted to the sintering aid characteristic temperatures.